2013
DOI: 10.1371/journal.pone.0057794
|View full text |Cite
|
Sign up to set email alerts
|

Aerobactin Synthesis Genes iucA and iucC Contribute to the Pathogenicity of Avian Pathogenic Escherichia coli O2 Strain E058

Abstract: Aerobactin genes are known to be present in virulent strains and absent from avirulent strains, but contributions of iucC and iucA, which are involved in aerobactin synthesis, to the pathogenicity of avian pathogenic Escherichia coli (APEC) have not been clarified. In this study, effects of double mutants (iucA/iutA or iucC/iutA) compared to those of single mutants (iucA, iucC or iutA) of aerobactin genes on the virulence of APEC strain E058 were examined both in vitro (aerobactin production, ingestion into HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 43 publications
2
33
0
1
Order By: Relevance
“…Tivendale et al (2004) demonstrated the ability of the three most virulent APEC strains to amplify the iucA gene in comparison with less virulent APEC strains. Other studies have also suggested that iucA plays an important role in the pathogenicity of APEC (Ling et al, 2013;Xiong et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Tivendale et al (2004) demonstrated the ability of the three most virulent APEC strains to amplify the iucA gene in comparison with less virulent APEC strains. Other studies have also suggested that iucA plays an important role in the pathogenicity of APEC (Ling et al, 2013;Xiong et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Aerobactin is synthesised by the iucABCD encoded gene (iron uptake chelate) and is taken up by the IutA-encoded receptor protein (Bindereif and Neilands, 1985;Ling et al, 2013). When compared to AFEC, aerobactin biosynthetic genes are more frequently detected in APEC and their incidence correlates with highly pathogenic strains (Dozois et al, 1992;Lafont et al, 1987;Linggood et al, 1987).…”
Section: Aerobactinmentioning
confidence: 99%
See 1 more Smart Citation
“…The salmochelin iron uptake system, encoded on the chromosome of Salmonella species and of several uropathogenic E. coli (UPEC) (95-98), has been recently associated with the ColV plasmids of APEC strains (90,92,99,100) as well as with non-ColV transmissible plasmids of UPEC and Klebsiella strains (101,102).…”
Section: Salmochelin Iron Uptake Systemmentioning
confidence: 99%
“…Among avian E. coli isolates, only the most virulent harbor the aerobactin genes, while these same genes are absent from nonvirulent and nonlethal isolates (88,89). Furthermore, aerobactin genes were expressed during infection, and defined deletion mutants in biosynthetic and transport genes resulted in decreased virulence in a chicken infection model (90)(91)(92). In whole-plasmid transcriptional studies, an additional gene, shiF, was upregulated during growth in human serum and urine and in a neonatal rat sepsis model (93,94).…”
mentioning
confidence: 99%